Angiopoietin: A Novel Neuroprotective/Neurotrophic Agent. (15th July 2019) - Yin, Jian; Gong, Ge; Liu, Xinhui
Abstract: Angiopoietin (Ang) is an angiogenic factor, but its neuroprotective and neurotrophic effects have recently come to light. Ang exerts neuroprotective effects by inhibiting neuronal apoptosis, protecting the blood–brain/blood-spinal cord barrier, reducing inflammation and promoting neovascularization. In addition, Ang can also promote neural development and neurite outgrowth via activation of the PI3K/Akt signaling pathway and binding to the Tie2 receptor and/or integrin receptor. In addition, Ang and vascular endothelial growth factor (VEGF) are known to interact in blood vessels in the nervous system and the combination of Ang and VEGF can mitigate the negative effects of VEGF, such as inflammation and local edema. These data indicated that Ang is a novel neuroprotective/neurotrophic factor, which may become a new tool for the treatment of nerve injury. Highlights: Angiopoietin inhibits neuronal apoptosis and promotes neurite outgrowth. Ang promotes angiogenesis, protects the blood–brain/blood spinal cord barrier and reduces inflammation Ang plays a neuroprotective or neurotrophic role by combining to Tie-2 or/and integrin receptors.